(untitled) (Conferencea, 2022)
The article discusses the pedagogical and psychological conditions for the development of professional and pedagogical creativity of teachers of primary education, the formation of creative qualities for the effective implementation of their professional activities, the existence of great pedagogical and psychological opportunities for the formation and development of creative qualities, theoretical research and practical The importance of the correct organization of activities, the versatility of the organization of professional creativity of future primary school teachers, as well as the complexity of the structure are interpreted.